2008
DOI: 10.1016/j.psychres.2007.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Errorless learning and memory performance in schizophrenia

Abstract: There is evidence that patients with schizophrenia have impaired explicit memory and intact implicit memory. The present study sought to replicate and extend that of O'Carroll et al. [O'Carroll, R.E., Russell, H.H., Lawrie, S.M. and Johnstone, E.C., 1999. Errorless learning and the cognitive rehabilitation of memory-impaired schizophrenic patients. Psychological Medicine 29, 105-112.] which reported that for memory-impaired patients with schizophrenia performance on a (cued) word recall task is enhanced using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Consistent with this, the correlation of positive symptom severity with nonpredictive cue scores was significantly greater than with predictive cues in experiment 2. A preferential increase in the attention to irrelevant cues represents an inefficient form of learning in schizophrenia36,37 and is an important precursor to the formation of delusions in some theories of psychosis, which view delusions as learned associations between unrelated events 21,23. Other research has also found that people with psychosis, and delusions in particular, learn to respond faster to irrelevant or nonreinforced stimuli in reaction-time tasks 3840.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this, the correlation of positive symptom severity with nonpredictive cue scores was significantly greater than with predictive cues in experiment 2. A preferential increase in the attention to irrelevant cues represents an inefficient form of learning in schizophrenia36,37 and is an important precursor to the formation of delusions in some theories of psychosis, which view delusions as learned associations between unrelated events 21,23. Other research has also found that people with psychosis, and delusions in particular, learn to respond faster to irrelevant or nonreinforced stimuli in reaction-time tasks 3840.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, EL has been used in interventions aimed at memory and executive deficits resulting from, among other causes, traumatic brain injury, Korsakoff’s syndrome, stroke, or schizophrenia,4,915 as well as in elderly populations with mild, moderate, and severe memory disorders (ie, dementia) 4. Grandmaison and Simard16 reviewed various memory stimulation and remediation programs for persons with Alzheimer’s disease and found the interventions that incorporated EL to be effective.…”
Section: Introductionmentioning
confidence: 99%
“…However, Evans and colleagues (2000) reported an advantage of EL for ABI patients only in some of their experiments. Other studies have found a beneficial effect of EL for persons diagnosed with schizophrenia (Kern et al, 2009;Mulholland, O'Donoghue, Meenagh, & Rushe, 2008; The advantage of EL has mainly been explained by mnemonic mechanisms related to long-term memory, both for clinical populations (Baddeley & Wilson, 1994;Hunkin et al, 1998;Kessels & de Haan, 2003a;Page et al, 2006) and for healthy adults (Anderson & Craik, 2006;Kessels et al, 2005). However, these explanations do not fully clarify why EL sometimes is the beneficial learning approach and at other times is not, both within the same population and across clinical diagnoses where the basic mnemonic mechanisms ought to be similar.…”
mentioning
confidence: 96%